You have two equations. One for the perimeter of a rectangle (known to be 62 inches), and one for the specified relationship between length and width:
2L + 2W = 62
L = 2W + 1
Substitute the second equation into the first:
2L + 2W = 62
2(2W + 1) + 2W = 62
4W + 2 + 2W = 62
6W = 60
W = 10
Use the second equation, now that we know W:
L = 2W + 1
L = 2*10 + 1
L = 21
You've calculated Length=21 inches, and Width=10 inches.
Use the perimeter equation to verify your answer:
2L + 2W =? 62
2*21 + 2*10 =? 62
42 + 20 =? 62
62 = 62
2007-06-18 13:19:33
·
answer #1
·
answered by McFate 7
·
1⤊
0⤋
Let the rectangle be w inches wide.
therefore its length is 2w+1 inch
Hence the perimeter of the rectangle
2(2w+1+w)=62
or(3w+1)=62/1=31
or,3w=31-1=30
or w=30/3=10 inches
and l=2*10=1=21 inches
therefore,the length of retangle is 21 inches and its width is 10 inches
2007-06-18 13:20:20
·
answer #2
·
answered by alpha 7
·
0⤊
0⤋
one million. different than for the question stating that the third component is 10cm decrease than the smallest component, that can not be actual, we will artwork by it something. the fringe (P) is the sum of all of the climate [ P = a + b + c] . we will call component b the smallest component. enable's say c is the third component listed in the above concern assertion, which says that the third component is 10cm decrease than the smallest component, or [ c = b - 10]. And the only component, as suggested, is 4 cases the smallest component, or [ a = 4 * b]. the fringe distance is given as 62cm, so our equation, after substitution, will become [ P = 62cm = (4*b) + b + (b-10cm) ] which reduces to [ 62cm = 6*b - 10cm]. subsequently, [ 72cm = 6*b ], which means b = 12 cm. Now that all of us understand b, we can clean up for a and c. [ a = 4 * b ], so a = 48cm, and [ c = b - 10cm ], so c = 2cm. component a = 48cm component b = 12cm component c = 2cm ================================= 2. the fringe of a rectangle, or the sum of all aspects, is [ P = W + W + L + L = 40ft ]. The assertion above says that the width is 8ft greater effective than two times the scale, or [ W = 8ft + 2*L ]. we've 2 equations for 2 unknowns. P = 40ft = 2*W + 2*L Substituting provides us [ 40ft = 2*(8ft + 2*L) + 2*L ] help provides us [ 40ft = 16ft + 4*L + 2*L ] which reduces to [ 24ft = 6*L ] or L = 4ft. Now that all of us understand L=4ft, we can clean up for W. [ 40ft = 2*W + 2*(4ft) ], or [ 40ft = 2*W + 8ft ], or [ 32ft = 2*W ], which means W = 16ft. W = 16ft L = 4ft =========================== 3. Assuming Sam's backyard is oblong, we can use the fringe equation P = 2*W + 2*L. all of us understand W = 38ft and L = 22ft. subsequently, P = 2*38ft + 2*22ft = one hundred twenty ft. with the aid of fact the fencing expenses $3.25 in step with foot, value = perimeter*value = 120ft * $3.25 = $390. finished value = $390.
2016-12-13 06:48:07
·
answer #3
·
answered by kreitman 4
·
0⤊
0⤋
Answers with Solutions
Qns. 1:
Length = l + 1
Width = l
Perimeter of Rectangle = 2 Lengths + 2 Widths
= 2 ( l + 1 ) + 2 ( l )
= 4l + 2
4l + 2 = 62
4l = 60
l = 60 / 4
= 15 in.
Substitute l = 15 in. into Length & Width,
Therefore,
Length = 15 + 1
= 16 in.
Width = 15 in.
Hope This Solutions Will Help In Answering Your Questions ;)
G0n9 G0n9™
Mathematician
2007-06-20 19:59:49
·
answer #4
·
answered by Kelvin 2
·
0⤊
0⤋
Just set up an equation.
P = 2L + 2W
L = 2W + 1
So, use the perimeter equation, plugging in the value for L and setting it equal to 62 inches, or...
62 = 2(2W + 1) + 2W
62 = (4W + 2) + 2W
62 = 6W + 2
60 = 6W
W = 10
So, L = 2W + 1 = 2(10) + 1 = 21
So, the dimesions for length times width are 21 inches x 10 inches.
2007-06-18 13:20:35
·
answer #5
·
answered by C-Wryte 3
·
0⤊
1⤋
1) perimeter = 2lenght + 2width
2) your condition: length = 2width + 1
And now: 62 = 2(2width + 1) + 2width
62 = 6width +2
60 = 6width ==> width = 10
And finally length = 2(10) + 1 = 21
2007-06-18 13:24:32
·
answer #6
·
answered by vahucel 6
·
0⤊
0⤋
I googled example of perimeter of rectangle and this came up. Exactly answers your question.
2007-06-19 06:57:30
·
answer #7
·
answered by JustHelping 2
·
0⤊
0⤋
L = 2W + 1
2(2W + 1) + 2W = 62
6W = 60
W = 10
L = 2W + 1 = 2*10 + 1
L = 21
.
2007-06-18 13:23:00
·
answer #8
·
answered by Robert L 7
·
0⤊
0⤋